A comparison of automated static dark stimuli with the Humphrey STATPAC program in glaucomatous visual field loss. Issue 3 (March 1994) - Mutlukan, E
Abstract : Visual field examination is conventionally performed with bright stimuli on a dark background. Dark stimuli on a bright background, however, may provide different information as light increases and decreases are subject to parallel processing in the visual pathway. Twenty five eyes with primary open angle glaucoma and visual field loss were examined with the Humphrey visual field analyser thresholding program 30-2 and the computer assisted moving eye campimeter (CAMEC) using static dark stimuli at four different Weber contrast levels of -10 (n = 9), -22 (n = 25), -37 (n = 14), and -76% (n = 25) on a cathode ray tube with a background luminance of 10 cd/m2. The cumulative results obtained with STATPAC 'pattern deviation' empirical probability maps and the results from each contrast of the dark stimulus at identical test locations were compared at eccentricity annuli bands of 4-9, 10-20, and 21-28 degrees. Dark stimuli of lower contrast provided higher abnormal point detection rates. Furthermore, visual field defects to the low contrast dark stimuli were more extensive than those to the luminous stimuli. In conclusion, dark stimuli allowed the delineation between glaucomatous field defects and the normal regions in the central visual field.